Предмет: Алгебра, автор: 228хулиган228

20 баллов! упростите выражения ПОД Б!

Приложения:

Ответы

Автор ответа: Regent1828
0
displaystyle b)..(a^{-3}-a^{-5})(a^{4}+a^{5})^{-1}*a^{9}=( frac{1}{a^{3}}- frac{1}{a^{5}})( frac{1}{a^{4}+a^{5}})*a^{9}= \  \= frac{a^{5}-a^{3}}{a^{8}(a^{4}+a^{5})}*a^{9}= frac{a^{6}-a^{4}}{a^{4}+a^{5}}= frac{a^{4}(a-1)(a+1)}{a^{4}(1+a)}=a-1;
Приложения:
Автор ответа: 228хулиган228
0
Спасибо!
Автор ответа: Regent1828
0
Не за что..))
Похожие вопросы
Предмет: Математика, автор: alexandra1007201